Considerations regarding the design of an online collaborative audit system. Issue 1 (4th January 2016) - Eni, Lucian Cristian
Abstract : Purpose: – The purpose of this paper is to introduce a new concept: the online collaborative audit system, and to design a prototype system at the national level for financial auditors, members of a supervisory body. Design/methodology/approach: – Conceptualization, modelling, analysis, imagination, scientific abstraction and review of legislation are the research methods used. Findings: – An online collaborative audit system is defined as an interorganizational system which uses the methods of collaborative intelligence among the stakeholders of the audit process (audit firms, auditees, supervision bodies) in a given geographical area (e.g. country) and which is based on the Internet. By assessing the design of the system, we could anticipate that an online collaborative system is feasible to implement. The main characteristics of an online collaborative audit system are geographical dispersion, collaboration between the stakeholders of the audit process, electronic management of the audit documents, online/continuous auditing and dynamic virtual teams, etc. Practical implications: – The system presented in this paper aims to cover the research gap which exists in this area and also to produce a change of paradigm in the sense that nowadays the technology allows us to move the audit results to an integrated national platform for audit stakeholders. In this way, the transparency of audit results increases and the role of audit becomes more predictive compared with the traditional way of performing an audit. Compared with the research in the field, the system presented in this paper is innovative in the sense that it not only allows online auditing but also gathers the national audit community in a virtual environment, which allows information sharing and improvement of information access. Social implications: – The online collaborative system for audit, which promotes collaboration between a large number of auditors and which is based on the networks of the supervision bodies, could be implemented not only by Romania, on which this research is based, but also by other countries. Originality/value: – The online collaborative systems for audit, which promotes collaboration between a large number of auditors and which is based on the networks of the supervision bodies, could be implemented not only by Romania but also by other countries.